Preparation method of lightweight heat-proof and heat-insulation integrated gradient aerogel material

By designing a lightweight, anti-insulation integrated gradient aerogel material composed of an alumina-resistant silicon coating, fiber-reinforced mullite aerogel and fiber-reinforced aluminum-silicon aerogel, the existing thermal insulation materials are solved. The problems of high density and high thermal conductivity in high temperature environments have achieved efficient heat insulation and temperature resistance in environments above 1600℃.

CN119430984APending Publication Date: 2025-02-14NANJING TECH UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411440621.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing thermal insulation materials exhibit high density and high thermal conductivity in high temperature environments, limiting their application in aerospace and other fields. Especially under harsh conditions above 1600℃, a single material is difficult to meet high-efficiency heat insulation and temperature resistance. Requirements.

Method used

A lightweight, anti-insulating integrated gradient aerogel material is designed, which consists of the outermost anti-oxidation aluminum silicon coating, the intermediate layer of fiber-reinforced mullite aerogel and the innermost layer of fiber-reinforced aluminum silicon Aerogel is composed of which effectively bonds the three layers of materials through high-temperature adhesives to form a material with low thermal conductivity, strong oxidation resistance and good heat insulation properties.

Benefits of technology

This material can withstand a 1600℃ hot service environment for up to 10 minutes under aerobic conditions, breaking through the temperature resistance limit of aerogels at 1600℃ aerobic conditions at home and abroad, and has wide application value in national defense science and technology, aerospace and thermal insulation areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430984A_ABST
    Figure CN119430984A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a lightweight heat prevention and insulation integrated gradient aerogel material, and designs a heat prevention and insulation integrated gradient aerogel material of which the outermost layer is an antioxidant aluminum-silicon coating, the middle layer is fiber-reinforced mullite aerogel and the innermost layer is of a fiber-reinforced aluminum-silicon aerogel structure. Wherein the aluminum-silicon coating on the outermost layer not only can directly prevent the impact of heat flow, but also can radiate part of heat to achieve a heat insulation effect due to high radiation coefficient and high emissivity of the aluminum-silicon coating. And the temperature resistance of the fiber-reinforced mullite aerogel in the middle layer can reach 1300 DEG C. And the outermost layer of fiber-reinforced aluminum-silicon aerogel has a strong heat insulation effect. The three layers of materials are effectively bonded through a high-temperature binder, and examination and numerical analysis prove that the material has low heat conductivity, strong oxidation resistance and good heat insulation performance, and can resist a 1600 DEG C thermal service environment for 10 minutes under an aerobic condition. The preparation method can be used for preparing the light heat-proof and heat-insulation integrated gradient aerogel material with a complete bulk structure, is low in cost and can realize large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to a method for preparing a lightweight thermal insulation integrated gradient aerogel material. The prepared lightweight thermal insulation integrated gradient aerogel material has broad application prospects in the fields of aerospace, high-temperature insulation, etc. Background technology:

[0002] With the rapid development of cutting-edge fields such as aerospace, new energy vehicle battery insulation materials, industrial kilns, and other military and civilian fields, lightweight, high-temperature, and high-strength thermal protection materials have become the key support for the development of extreme environment applications such as hypersonic aircraft thermal protection systems. However, some current advanced thermal insulation materials are limited in their further development as efficient thermal insulation materials due to their high density and high thermal conductivity. Therefore, many researchers are committed to developing porous materials with low bulk density, high thermal resistance, and low thermal conductivity. Aerogel has a nanoscale pore size distribution, and its mean free path (~50nm) is smaller than the mean free path of air (~69nm), so it is difficult for air molecules to pass through aerogel, so aerogel has the characteristics of low density and low thermal conductivity. At present, the popular materials in the field of high-temperature aerogels include aluminum-silicon aerogels and ceramic aerogels. For example, Wei Jianzheng et al. of Harbin Institute of Technology (CN201710081652.6) disclosed a method for preparing a flexible thermal insulation composite material based on aluminum-silicon composite aerogel with mullite fiber as the reinforcing phase. The material has good temperature resistance and thermal shock resistance, but it is difficult to obtain industrial raw materials for mullite fiber, and it is impossible to achieve industrial large-scale production. However, the use temperature of the material is only 1200°C. Guo Anran et al. of Tianjin University (CN201910393603.5) used mullite nanofibers combined with silica sol and prepared a lightweight and thermally insulating mullite nanofiber aerogel by gel injection molding of an acrylamide system. The preparation process of the invention is simple, but it is difficult to obtain industrial raw materials for mullite nanofibers, and the use temperature of the material is only 1300°C. Our previous research (CN201210405546.6) invented a high-temperature resistant silicon carbide aerogel thermal insulation composite material using aluminum silicate fiber felt as a reinforcement. This method uses simple materials and has a simple process, but the maximum temperature resistance is only 1400°C. With the development of aerospace thermal protection technology, higher requirements have been put forward for the density, temperature resistance, heat insulation, and mechanical properties of thermal insulation materials. Even under some harsh conditions, the requirements for thermal insulation materials reach above 1600°C, and a single material is no longer competent. For example, when an aerospace vehicle flies in the atmosphere, the high temperature environment generated locally reaches 1600°C for a long time. At present, there are few reports on lightweight thermal insulation integrated gradient aerogel materials that can withstand the 1600°C hot service environment for a long time and can be industrially produced. Summary of the invention:

[0003] The purpose of the present invention is to improve the deficiencies of the prior art and provide a preparation study of a lightweight integrated thermal insulation gradient material. A lightweight integrated thermal insulation gradient aerogel material is designed, wherein the outermost layer is an anti-oxidation aluminum silicon coating, the middle layer is a high temperature resistant, high strength fiber reinforced mullite aerogel, and the innermost layer is a low density and low thermal conductivity fiber reinforced aluminum silicon aerogel. The outermost aluminum silicon coating can not only directly prevent the impact of heat flow, but its high emissivity and high emissivity can also radiate part of the heat to achieve the effect of thermal insulation. The temperature resistance of the middle layer fiber reinforced mullite aerogel can reach 1300°C. The outermost fiber reinforced aluminum silicon aerogel has a strong thermal insulation effect. By effectively bonding the three layers of materials with a high temperature adhesive, it is proved through assessment and numerical analysis that the material has low thermal conductivity, strong antioxidant ability and good thermal insulation performance. It can withstand a 1600°C hot service environment for up to 10 minutes under aerobic conditions.

[0004] The specific technical solution of the present invention is: a method for preparing a lightweight thermal insulation integrated gradient aerogel material, and the specific steps are as follows:

[0005] (1) Preparation of slurry (1a) Al2O3 powder, SiO2 powder, ethanol and sodium carboxymethyl cellulose are mixed in proportion and ball-milled for 1 to 6 hours to obtain a slurry;

[0006] (2) Preparation of fiber-reinforced mullite aerogel (2a) An aluminum source, a silicon source, ethanol, and water are mixed in proportion and stirred for 0.1 to 5 hours to obtain an aluminum silica sol;

[0007] (2b) mixing a phenolic compound, an aldehyde compound, and ethanol in proportion and stirring them uniformly to obtain a phenolic solution; (2c) mixing the aluminum silica sol obtained in step (2a) and step (2b) and the phenolic solution in proportion and stirring them uniformly for 10 to 60 minutes, adding propylene oxide, continuing to stir for 1 to 30 minutes, and then pouring it into a mold containing fiber felt to allow the liquid to completely impregnate the fiber felt, allowing it to gel and age at 30 to 70° C., standing it for 1 to 24 hours, and performing solvent replacement;

[0008] (2d) subjecting the wet gel obtained in step (2c) to supercritical carbon dioxide drying to obtain a precursor aerogel; (2e) subjecting the aerogel obtained in step (2d) to heat treatment under a protective atmosphere to obtain a fiber-reinforced mullite aerogel;

[0009] (3) Fiber-reinforced aluminum silicate aerogel (3a) An aluminum source, a silicon source, ethanol, and water are mixed in proportion and stirred for 0.1 to 5 hours to obtain an aluminum silicate sol;

[0010] (3b) adding propylene oxide to the aluminum silica sol obtained in step (3a), and then pouring it into a mold containing fiber felt, so that the liquid completely impregnates the fiber felt, waits for the gel to age, and then replaces the gel part with solvent;

[0011] (3c) subjecting the wet gel after the solvent replacement in step (3b) to supercritical drying with ethanol to obtain a fiber-reinforced aluminum silicate aerogel;

[0012] (4) Preparation of lightweight thermal insulation integrated gradient aerogel (4a) The slurry obtained in step (1) is brushed on the upper surface of the fiber-reinforced mullite aerogel obtained in step (2), and dried at 50 to 200° C. for 0.5 to 5 h;

[0013] (4b) placing the dried sample obtained in step (4a) in a graphite crucible filled with silicon powder, and performing heat treatment under a protective atmosphere to obtain a fiber-reinforced mullite aerogel coated with an oxidation-resistant aluminum-silicon coating;

[0014] (4c) The other side of the fiber-reinforced mullite aerogel coated with an anti-oxidation aluminum-silicon coating obtained in step (4b) and the fiber-reinforced aluminum-silicon aerogel obtained in step (3) are bonded with a high-temperature adhesive, and the mixture is kept warm in an oven at 30 to 100° C. for 2 to 24 hours to obtain a lightweight, heat-insulating, integrated gradient aerogel material.

[0015] Preferably, the Al2O3 powder, SiO2 powder, ethanol and sodium carboxymethyl cellulose described in step (1a) are ball-milled in a mass ratio of 1:(0.1-3):(1-5):(0.1-2), wherein the ball mill speed is 100-600 rpm and the material-to-ball ratio is 1:(1-3).

[0016] Preferably, the aluminum source in step (2a) is one or more of aluminum chloride hexahydrate, aluminum nitrate nonahydrate or aluminum sulfate 18hydrate; the silicon source is one or more of tetramethyl silicate, tetraethyl orthosilicate, tetraisopropyl silicate, tetrabutyl silicate or tetraphenyl silicate; wherein the silicon source, the aluminum source, ethanol and water are mixed in a molar ratio of 1:(1-5):(5-20):(20-60); the phenolic compound in step (2b) is one or more of catechol, resorcinol, hydroquinone, cresol or pyrogallol; the aldehyde compound is one or more of formaldehyde, acetaldehyde, butyraldehyde, cinnamaldehyde or anisaldehyde; wherein the phenolic compound, the aldehyde compound and ethanol are mixed in a molar ratio of 1:(1-5):(2-10).

[0017] Preferably, the mass ratio of the aluminum silica sol and the phenolic solution in step (2c) is 1:(0.1-1); the molar ratio of propylene oxide to aluminum source is 1:(0.1-5); the fiber felt is one or more of mullite fiber felt, polycrystalline alumina fiber felt or high silica fiber felt; the replacement solvent is one or more of ethanol, methanol, acetone, n-pentanol or isopropanol; the number of replacements is 5-15 times, with an interval of 6-12 hours each time; the carbon dioxide supercritical drying in step (2d) uses carbon dioxide as the drying medium, the reaction temperature is 40-70°C, the drying pressure is 8-15MPa, the degassing rate is 4-16L / min, and the drying time is 5-14h; the inert atmosphere in step (2e) is one or more of argon or nitrogen; the heat treatment temperature is 800-1500°C, the heating rate is 2-8°C / min, and the insulation time is 2-7h.

[0018] Preferably, the aluminum source in step (3a) is one or more of aluminum chloride hexahydrate, aluminum nitrate nonahydrate or aluminum sulfate octahydrate; the silicon source is one or more of tetramethyl silicate, tetraethyl orthosilicate, tetraisopropyl silicate, tetrabutyl silicate or tetraphenyl silicate; wherein the silicon source, aluminum source, ethanol and water are mixed in a molar ratio of 1: (1-5): (10-40): (30-50). 6. The preparation method according to claim 1, characterized in that the molar ratio of propylene oxide to aluminum source in step (3b) is 1: (0.1-5); the fiber felt is one or more of aluminum silicate fiber felt, glass fiber felt or basalt fiber felt; the replacement solvent is one or more of ethanol, methanol, acetone, n-pentanol or isopropanol; the replacement times are 5-15 times, each time interval is 6-12 hours.

[0019] Preferably, the ethanol supercritical drying method described in step (3c) adopts nitrogen protection, the drying temperature is 255-280° C., the pressure of the high-pressure reactor is controlled at 8-12 MPa, and the reaction time is 2-6 h.

[0020] Preferably, the coating thickness of the paint in step (4a) is 50 to 500 μm.

[0021] Preferably, the protective atmosphere in step (4b) is one of argon and nitrogen or a mixture thereof; the heat treatment temperature is 800-1500°C, the heating rate is 2-8°C / min, and the insulation time is 0.5-5h.

[0022] Preferably, the high temperature binder in step (4c) is one or more of aluminum silicate, magnesium phosphate, sodium sulfate or potassium borate.

[0023] The lightweight heat-insulating integrated gradient aerogel material prepared by the present invention consists of three parts, of which the outermost layer is an anti-oxidation aluminum-silicon coating, which can not only directly prevent the impact of heat flow, but also its high emissivity and high emissivity can radiate part of the heat to achieve the effect of heat insulation. The middle layer is a fiber-reinforced mullite aerogel, which has a temperature resistance of up to 1300°C. The innermost layer is a fiber-reinforced aluminum-silicon aerogel with a strong heat-insulating effect. The lightweight heat-insulating integrated gradient aerogel material obtained by effectively bonding these three parts of the material with a high-temperature adhesive can withstand a hot service environment of 1600°C for up to 10 minutes under aerobic conditions. Preferably, the total thickness of the prepared lightweight heat-insulating integrated gradient aerogel material is 50-55mm, of which the thickness of the fiber-reinforced aluminum-silicon aerogel is 10-40mm.

[0024] Beneficial effects:

[0025] The method of the present invention and the method for preparing a lightweight thermal insulation integrated gradient aerogel material prepared by the method have the following characteristics:

[0026] (1) The raw materials of this process are simple and easy to obtain, with low energy consumption, high efficiency and low cost, and can be industrialized by large-scale production.

[0027] (2) The invention provides a novel method for preparing a lightweight integrated thermal insulation gradient material with a three-layer structure, wherein the outermost layer is an anti-oxidation aluminum silicon coating, which can not only directly block the impact of heat flow, but also radiate part of the heat with its high emissivity and high emissivity to achieve a thermal insulation effect. The middle layer is a fiber-reinforced mullite aerogel, which has a temperature resistance of up to 1300°C. The innermost layer is a fiber-reinforced aluminum silicon aerogel, which has a strong thermal insulation effect. The three layers of material are effectively bonded to retain the low thermal conductivity of the material while making the material as a whole have a higher temperature resistance.

[0028] (3) The prepared lightweight, heat-insulating integrated gradient aerogel material has a complete large block structure, which for the first time breaks through the bottleneck of the temperature resistance limit of aerogels under aerobic conditions at home and abroad of 1600°C. It has a wide range of application value in the fields of national defense science and technology, aerospace, thermal insulation, etc. Description of the drawings:

[0029] Figure 1 This is a physical picture of the lightweight, heat-insulating, integrated gradient aerogel material obtained in Example 1.

[0030] Figure 2 This is a back temperature assessment curve of the lightweight thermal insulation integrated gradient aerogel material obtained in Example 2 at 1600°C.

[0031] Figure 3This is a scanning electron microscope image of the interface between the coating and the fiber-reinforced mullite aerogel of the lightweight thermal insulation integrated gradient aerogel material obtained in Example 3 before and after the test at 1600°C. Among them, ac is before the test, and df is after the test. Specific implementation method:

[0032] The present invention is further described below with reference to examples, but the protection scope is not limited thereto.

[0033] Example 1

[0034] Al 2 O 3 Powder, SiO 2The powder, ethanol, and sodium carboxymethyl cellulose were mixed in a mass ratio of 1:0.1:1:0.1 and ball milled, wherein the material-ball ratio was 1:1, the ball mill speed was 100 rpm, and the ball milling time was 6 hours, thereby obtaining an aluminum silicon coating. Aluminum chloride hexahydrate, tetramethyl silicate, ethanol, and water were mixed in a molar ratio of 1:1:5:20 at 20°C and stirred for 0.1 hours to obtain an aluminum silicate sol. Pyrocatechol, formaldehyde, and ethanol were mixed in a molar ratio of 1:1:2 at 20°C and stirred evenly to obtain a phenolic solution. Then, the aluminum silica sol and phenolic solution were mixed in a mass ratio of 1:0.1 and stirred for 10 minutes, and then a certain amount of propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum chloride hexahydrate was 1:0.1, and the stirring was continued for 1 minute, and it was poured into a mold containing mullite fiber felt, so that the liquid completely impregnated the fiber felt, and the gel was aged at 30°C and stood for 24 hours, and then the solvent was replaced with ethanol, and the number of replacements was 5 times, each time with an interval of 12 hours. After the replacement was completed, it was supercritically dried with carbon dioxide, wherein the drying temperature was 40°C, the drying pressure was 8MPa, the degassing rate was 4L / min, and the drying time was 5h. Then the obtained precursor aerogel was heat treated at 800°C in an argon atmosphere, wherein the heating rate was 2°C / min, and the insulation time was 2h, thereby obtaining a fiber-reinforced mullite aerogel. Aluminum nitrate nonahydrate, tetraethyl orthosilicate, ethanol, and water were stirred at 20°C for 5 hours in a molar ratio of 1:1:10:30 to obtain aluminum silicate sol, and then propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum nitrate nonahydrate was 1:0.1. It was poured into a mold containing aluminum silicate fiber felt, so that the liquid completely impregnated the fiber felt, and the gel was aged at 20°C, and then the gel part was solvent replaced with methanol, the replacement number was 5 times, and each time was 12 hours. After the replacement was completed, ethanol supercritical drying was carried out, wherein the drying temperature was 255°C, the drying pressure was 8MPa, and the drying time was 2h, thereby obtaining fiber-reinforced aluminum silicate aerogel. Finally, the slurry was brushed on the upper surface of the fiber reinforced mullite aerogel to a thickness of 50 μm and dried at 50 °C for 5 h. It was then placed in a graphite crucible filled with silicon powder and heat treated at 800 °C in a nitrogen atmosphere, with a heating rate of 2 °C / min and a holding time of 0.5 h to obtain a fiber reinforced mullite aerogel with an antioxidant coating. The aerogel was then effectively bonded to the fiber reinforced aluminum silicate aerogel using aluminum silicate and kept in an oven at 30 °C for 24 h to obtain a lightweight, heat-insulating, integrated gradient aerogel material with a three-layer structure. Figure 1This is a photo of a lightweight, heat-insulating, integrated gradient aerogel material with a complete structure. The total thickness of the material is 50 mm, of which the thickness of the fiber-reinforced aluminum-silicon aerogel layer is 10 mm. Characterization shows that the thermal conductivity of the material is 0.018 W / (m·K) at room temperature and 0.152 W / (m·K) at 1200°C. After 10 minutes of testing at 1600°C, the back temperature was measured to be only 120.3°C, and there was no obvious shrinkage of the sample before and after the test. The coating after the test was characterized using a scanning electron microscope, and it was found that the coating was loose and porous and not densified, indicating that the material has excellent antioxidant properties.

[0035] Example 2

[0036] Al 2 O 3 Powder, SiO 2The powder, ethanol, and sodium carboxymethyl cellulose were mixed in a mass ratio of 1:3:5:2 and ball milled, wherein the material-ball ratio was 1:3, the ball mill speed was 600 rpm, and the ball milling time was 1 hour, thereby obtaining a slurry. Aluminum nitrate nonahydrate, tetraisopropyl silicate, ethanol, and water were mixed in a molar ratio of 1:5:20:60 at 40°C and stirred for 1 hour to obtain an aluminum silica sol. Resorcinol, acetaldehyde, and ethanol were mixed in a molar ratio of 1:5:10 at 40°C and stirred evenly to obtain a phenolic solution. Then, the aluminum silica sol and phenolic solution were mixed in a mass ratio of 1:1 and stirred for 60 minutes, and then a certain amount of propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum nitrate nine hydrate was 1:5, and it was poured into a mold containing polycrystalline alumina fiber felt, so that the liquid completely impregnated the fiber felt, and continued to stir for 10 minutes. The gel was aged at 70°C and stood for 1 hour, and then the solvent was replaced with methanol, and the number of replacements was 15 times, each time at an interval of 6 hours. After the replacement was completed, it was supercritically dried with carbon dioxide, wherein the drying temperature was 70°C, the drying pressure was 15MPa, the degassing rate was 16L / min, and the drying time was 14h. Then the obtained precursor aerogel was heat treated at 1500°C in an argon atmosphere, wherein the heating rate was 8°C / min, and the insulation time was 7h, thereby obtaining a fiber-reinforced mullite aerogel. Aluminum sulfate 18hydrate, tetramethyl silicate, ethanol and water were mixed at a molar ratio of 1:5:40:50 at 25°C and stirred for 3 hours to obtain aluminum silica sol, and then propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum sulfate 18hydrate was 1:5. It was poured into a mold containing glass fiber felt, so that the liquid completely impregnated the fiber felt, and the gel was aged at 40°C, and then the gel part was solvent replaced with ethanol, the number of replacements was 15 times, and each time was 6 hours. After the replacement was completed, ethanol supercritical drying was carried out, wherein the drying temperature was 280°C, the drying pressure was 12MPa, and the drying time was 6 hours, thereby obtaining fiber-reinforced aluminum silicate aerogel. Finally, the slurry was brushed on the upper surface of the fiber-reinforced mullite aerogel to a thickness of 500 μm, dried at 200 ° C for 0.5 h, and then placed in a graphite crucible filled with silicon powder for heat treatment at 1500 ° C in an argon atmosphere, with a heating rate of 8 ° C / min and a holding time of 5 h, thereby obtaining a fiber-reinforced mullite aerogel with an antioxidant coating. It was effectively bonded to the fiber-reinforced aluminum-silicon aerogel using magnesium phosphate and kept in an oven at 100 ° C for 2 h to obtain a lightweight, heat-insulating, integrated gradient aerogel material. The total thickness of the material is 55 mm, of which the thickness of the fiber-reinforced aluminum-silicon aerogel layer is 40 mm, and the thermal conductivity of the material is 0.015 W / (m·K) at room temperature and 0.155 W / (m·K) at 1200 ° C after characterization. Figure 2The back temperature test curve of the material at 1600℃ is shown in Figure 1. After 10 minutes of testing, the back temperature is only 122.7℃, and there is no obvious shrinkage of the sample before and after the test. The coating after the test was characterized by scanning electron microscopy, and it was found that the coating was loose and porous and not densified, indicating that the material has excellent antioxidant properties.

[0037] Example 3

[0038] Al 2 O 3 Powder, SiO 2The powder, ethanol, and sodium carboxymethyl cellulose were mixed in a mass ratio of 1:0.5:2:0.3 and ball-milled, wherein the material-ball ratio was 1:2, the ball mill speed was 300 rpm, and the ball milling time was 5 hours, thereby obtaining a slurry. Aluminum sulfate 18hydrate, tetraethyl orthosilicate, ethanol, and water were mixed in a molar ratio of 1:2:8:30 at 25°C and stirred for 5 hours to obtain aluminum silicate sol. Hydroquinone, butyraldehyde, and ethanol were mixed in a molar ratio of 1:2:5 at 25°C and stirred evenly to obtain a phenolic solution. Then, the aluminum silica sol and phenolic solution were mixed in a mass ratio of 1:0.3 and stirred for 20 minutes, and then a certain amount of propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum sulfate 18 hydrate was 1:0.5, and the stirring was continued for 30 minutes, and it was poured into a mold containing high silica fiber felt, so that the liquid completely impregnated the fiber felt, and the gel was aged at 50°C and stood for 8 hours, and then the solvent was replaced with acetone, and the number of replacements was 8 times, each interval was 9 hours. After the replacement was completed, it was supercritically dried with carbon dioxide, wherein the drying temperature was 50°C, the drying pressure was 10MPa, the degassing rate was 8L / min, and the drying time was 8h. Then the obtained precursor aerogel was heat treated at 1450°C in an argon atmosphere, wherein the heating rate was 3°C / min, and the insulation time was 3h, thereby obtaining a fiber-reinforced mullite aerogel. Aluminum chlorohydrate, tetraisopropyl silicate, ethanol and water were mixed at a molar ratio of 1:2:20:40 at 30°C and stirred for 2h to obtain aluminum silica sol, and then a certain amount of propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum chlorohydrate was 1:1. It was poured into a mold containing basalt fiber felt, so that the liquid completely impregnated the fiber felt, and the gel was aged at 25°C, and then the gel part was solvent replaced with acetone, the replacement number was 8 times, and each time was 9h. After the replacement was completed, ethanol supercritical drying was carried out, wherein the drying temperature was 260°C, the drying pressure was 9MPa, and the drying time was 3h, thereby obtaining fiber-reinforced aluminum silicate aerogel. Finally, the slurry was brushed on the upper surface of the fiber-reinforced mullite aerogel to a thickness of 100 μm, and dried at 100 ° C for 1 hour, and then placed in a graphite crucible filled with silicon powder for heat treatment at 1200 ° C in a nitrogen atmosphere, wherein the heating rate was 3 ° C / min, and the holding time was 2 hours, thereby obtaining a fiber-reinforced mullite aerogel with an antioxidant coating, which was effectively bonded to the fiber-reinforced aluminum-silicon aerogel using sodium sulfate, and kept in a 50 ° C oven for 18 hours, thereby obtaining a lightweight thermal insulation integrated gradient aerogel material. The total thickness of the material is 53 mm, of which the thickness of the fiber-reinforced aluminum-silicon aerogel layer is 20 mm, and after characterization, the thermal conductivity of the material is 0.016 W / (m·K) at room temperature and 0.149 W / (m·K) at 1200 ° C. After the material was tested at 1600 ° C for 10 minutes, the back temperature was only 121.5 ° C, and there was no obvious shrinkage of the sample before and after the test. Figure 3This is a scanning electron microscope image of the interface between the coating and the fiber-reinforced mullite aerogel before and after the material is tested at 1600°C. The scanning electron microscope image shows that the coating after the test is loose and porous and has not been densified, thus proving that the material has excellent antioxidant properties.

[0039] Example 4

[0040] Al 2 O 3 Powder, SiO 2The powder, ethanol, and sodium carboxymethyl cellulose were mixed in a mass ratio of 1:1:3:0.8 and ball-milled, wherein the material-ball ratio was 1:1.5, the ball mill speed was 400 rpm, and the ball milling time was 3 hours, thereby obtaining a slurry. Aluminum chloride hexahydrate, tetrabutyl silicate, ethanol, and water were mixed in a molar ratio of 1:3:15:40 at 30°C and stirred for 2 hours to obtain an aluminum silica sol. Cresol, cinnamaldehyde, and ethanol were mixed in a molar ratio of 1:3:7 at 30°C and stirred evenly to obtain a phenolic solution. Then, the aluminum silica sol and phenolic solution were mixed in a mass ratio of 1:0.5 and stirred for 30 minutes, and then a certain amount of propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum chloride hexahydrate was 1:2, and the stirring was continued for 15 minutes, and it was poured into a mold containing mullite fiber felt, so that the liquid completely impregnated the fiber felt, and the gel was aged at 40°C and stood for 12 hours, and then the solvent was replaced with n-pentanol, and the number of replacements was 9 times, each interval was 8 hours. After the replacement was completed, it was subjected to supercritical carbon dioxide drying, wherein the drying temperature was 55°C, the drying pressure was 12MPa, the degassing rate was 10L / min, and the drying time was 10h. Then the obtained precursor aerogel was heat treated at 1300°C in an argon atmosphere, wherein the heating rate was 5°C / min, and the insulation time was 4h, thereby obtaining a fiber-reinforced mullite aerogel. Aluminum nitrate nonahydrate, tetrabutyl silicate, ethanol and water were mixed at a molar ratio of 1:3:30:35 at 35°C and stirred for 1h to obtain aluminum silicate sol, and then a certain amount of propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum nitrate nonahydrate was 1:1.5. It was poured into a mold containing aluminum silicate fiber felt, so that the liquid completely impregnated the fiber felt, and the gel was aged at 30°C, and then the gel part was solvent replaced with n-pentanol, the number of replacements was 9 times, and each interval was 8h. After the replacement was completed, ethanol supercritical drying was carried out, wherein the drying temperature was 265°C, the drying pressure was 10MPa, and the drying time was 4h, thereby obtaining fiber-reinforced aluminum silicate aerogel. Finally, the slurry was brushed on the upper surface of the fiber-reinforced mullite aerogel to a thickness of 200 μm, and dried at 150 ° C for 3 hours, and then placed in a graphite crucible filled with silicon powder and heat treated at 1350 ° C in an argon atmosphere, wherein the heating rate was 5 ° C / min, and the holding time was 3 hours, thereby obtaining a fiber-reinforced mullite aerogel with an antioxidant coating, which was effectively bonded to the fiber-reinforced aluminum-silicon aerogel with potassium borate, and kept in a 70 ° C oven for 12 hours, thereby obtaining a lightweight thermal insulation integrated gradient aerogel material. The total thickness of the material is 51 mm, of which the thickness of the fiber-reinforced aluminum-silicon aerogel layer is 25 mm, and after characterization, the thermal conductivity of the material is 0.019 W / (m·K) at room temperature and 0.150 W / (m·K) at 1200 ° C. After the material was tested at 1600 ° C for 10 minutes, the back temperature was only 123.6 ° C, and there was no obvious shrinkage of the sample before and after the test.The coating was characterized using a scanning electron microscope and found to be loose and porous and not densified, indicating that the material has excellent antioxidant properties.

[0041] Example 5

[0042] Al 2 O 3 Powder, SiO 2The powder, ethanol, and sodium carboxymethyl cellulose were mixed in a mass ratio of 1:2:4:1 and ball milled, wherein the material-ball ratio was 1:2.5, the ball mill speed was 500 rpm, and the ball milling time was 2 hours, thereby obtaining a slurry. Aluminum nitrate nonahydrate, tetraphenyl silicate, ethanol, and water were mixed in a molar ratio of 1:4:18:50 at 35°C and stirred for 3 hours to obtain an aluminum silica sol. Pyrogallol, anisaldehyde, and ethanol were mixed in a molar ratio of 1:4:9 at 35°C and stirred evenly to obtain a phenolic solution. Then, the aluminum silica sol and phenolic solution were mixed in a mass ratio of 1:0.8 and stirred for 50 minutes, and then a certain amount of propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum nitrate nine hydrate was 1:3, and the stirring was continued for 20 minutes, and it was poured into a mold containing polycrystalline alumina fiber felt, so that the liquid completely impregnated the fiber felt, and the gel was aged at 60°C and stood for 20 hours, and then the solvent was replaced with isopropanol, and the number of replacements was 12 times, each interval was 7 hours. After the replacement was completed, it was supercritically dried with carbon dioxide, wherein the drying temperature was 60°C, the drying pressure was 13MPa, the degassing rate was 14L / min, and the drying time was 12 hours. Then the obtained precursor aerogel was heat treated at 1200°C in an argon atmosphere, wherein the heating rate was 7°C / min, and the insulation time was 5 hours, thereby obtaining a fiber-reinforced mullite aerogel. Aluminum sulfate 18hydrate, tetraphenyl silicate, ethanol and water were mixed at a molar ratio of 1:4:25:45 at 40°C and stirred for 0.1h to obtain aluminum silica sol, and then a certain amount of propylene oxide was added, wherein the molar ratio of propylene oxide to aluminum sulfate 18hydrate was 1:4. It was poured into a mold containing glass fiber felt, so that the liquid completely impregnated the fiber felt, and the gel was aged at 35°C, and then the gel part was solvent replaced with isopropanol, the replacement number was 12 times, and each time was 7h. After the replacement was completed, ethanol supercritical drying was carried out, wherein the drying temperature was 270°C, the drying pressure was 11MPa, and the drying time was 5h, thereby obtaining fiber-reinforced aluminum silicate aerogel. Finally, the slurry was brushed on the upper surface of the fiber-reinforced mullite aerogel to 300μm, and dried at 180℃ for 3.5h, and then placed in a graphite crucible filled with silicon powder for heat treatment at 1450℃ in a nitrogen atmosphere, where the heating rate was 6℃ / min and the insulation time was 4h, thereby obtaining a fiber-reinforced mullite aerogel with an antioxidant coating, and then it was effectively bonded to the fiber-reinforced aluminum-silicon aerogel with aluminum silicate, and kept in an oven at 80℃ for 8h, thereby obtaining a lightweight thermal insulation integrated gradient aerogel material. The total thickness of the material is 54mm, of which the thickness of the fiber-reinforced aluminum-silicon aerogel layer is 30mm, and after characterization, the thermal conductivity of the material is 0.017W / (m·K) at room temperature and 0.155W / (m·K) at 1200℃. And after the material was tested at 1600℃ for 10min, the back temperature was only 122.2℃, and there was no obvious shrinkage of the sample before and after the test.The coating was characterized using a scanning electron microscope and found to be loose and porous and not densified, indicating that the material has excellent antioxidant properties.

Claims

1. A method for preparing a lightweight thermal insulation integrated gradient aerogel material, the specific steps of which are as follows: (1) Preparation of slurry (1a) Al2O3 powder, SiO2 powder, ethanol, and sodium carboxymethyl cellulose are mixed in proportion and ball-milled for 1 to 6 hours to obtain a slurry; (2) Preparation of fiber-reinforced mullite aerogel (2a) mixing an aluminum source, a silicon source, ethanol, and water in proportion and stirring for 0.1 to 5 hours to obtain an aluminum silica sol; (2b) mixing a phenolic compound, an aldehyde compound, and ethanol in proportion and stirring them uniformly to obtain a phenolic solution; (2c) mixing the aluminum silica sol obtained in step (2a) and step (2b) and the phenolic solution in proportion and stirring them uniformly for 10 to 60 minutes, adding propylene oxide, continuing to stir for 1 to 30 minutes, and then pouring it into a mold containing fiber felt to allow the liquid to completely impregnate the fiber felt, allowing it to gel and age at 30 to 70° C., standing it for 1 to 24 hours, and performing solvent replacement; (2d) subjecting the wet gel obtained in step (2c) to supercritical carbon dioxide drying to obtain a precursor aerogel; (2e) subjecting the aerogel obtained in step (2d) to heat treatment under a protective atmosphere to obtain a fiber-reinforced mullite aerogel; (3) Fiber-reinforced aluminum-silicon aerogel (3a) mixing an aluminum source, a silicon source, ethanol, and water in proportion and stirring for 0.1 to 5 hours to obtain an aluminum silica sol; (3b) adding propylene oxide to the aluminum silica sol obtained in step (3a), and then pouring it into a mold containing fiber felt, so that the liquid completely impregnates the fiber felt, waits for the gel to age, and then replaces the gel part with solvent; (3c) subjecting the wet gel after the solvent replacement in step (3b) to supercritical drying with ethanol to obtain a fiber-reinforced aluminum silicate aerogel; (4) Preparation of lightweight thermal insulation integrated gradient aerogel (4a) brushing the slurry obtained in step (1) onto the upper surface of the fiber-reinforced mullite aerogel obtained in step (2), and drying at 50 to 200° C. for 0.5 to 5 h; (4b) placing the dried sample obtained in step (4a) in a graphite crucible filled with silicon powder, and performing heat treatment under a protective atmosphere to obtain a fiber-reinforced mullite aerogel coated with an oxidation-resistant aluminum-silicon coating; (4c) The other side of the fiber-reinforced mullite aerogel coated with an anti-oxidation aluminum-silicon coating obtained in step (4b) and the fiber-reinforced aluminum-silicon aerogel obtained in step (3) are bonded with a high-temperature adhesive, and the mixture is kept warm in an oven at 30 to 100° C. for 2 to 24 hours to obtain a lightweight, heat-insulating, integrated gradient aerogel material.

2. The preparation method according to claim 1, characterized in that Preferably, the Al2O3 powder, SiO2 powder, ethanol and sodium carboxymethyl cellulose described in step (1a) are ball-milled in a mass ratio of 1:(0.1-3):(1-5):(0.1-2), wherein the ball mill speed is 100-600 rpm and the material-to-ball ratio is 1:(1-3).

3. The preparation method according to claim 1, characterized in that The aluminum source in step (2a) is one or more of aluminum chloride hexahydrate, aluminum nitrate nonahydrate or aluminum sulfate 18hydrate; the silicon source is one or more of tetramethyl silicate, tetraethyl orthosilicate, tetraisopropyl silicate, tetrabutyl silicate or tetraphenyl silicate; wherein The silicon source, the aluminum source, the ethanol and the water are mixed in a molar ratio of 1:(1-5):(5-20):(20-60); the phenolic compound in step (2b) is one or more of catechol, resorcinol, hydroquinone, cresol or pyrogallol; the aldehyde compound is one or more of formaldehyde, acetaldehyde, butyraldehyde, cinnamaldehyde or anisaldehyde; wherein the phenolic compound, the aldehyde compound and the ethanol are mixed in a molar ratio of 1:(1-5):(2-10).

4. The preparation method according to claim 1, characterized in that The mass ratio of the aluminum silica sol and the phenolic solution described in step (2c) is 1:(0.1-1); the molar ratio of propylene oxide to aluminum source is 1:(0.1-5); the fiber felt is one or more of mullite fiber felt, polycrystalline alumina fiber felt or high silica fiber felt; the replacement solvent is one or more of ethanol, methanol, acetone, n-pentanol or isopropanol; the number of replacements is 5-15 times, with an interval of 6-12 hours each time; the carbon dioxide supercritical drying described in step (2d) uses carbon dioxide as the drying medium, the reaction temperature is 40-70°C, the drying pressure is 8-15MPa, the degassing rate is 4-16L / min, and the drying time is 5-14h; the inert atmosphere described in step (2e) is one or more of argon or nitrogen; the heat treatment temperature is 800-1500°C, the heating rate is 2-8°C / min, and the insulation time is 2-7h.

5. The preparation method according to claim 1, characterized in that The aluminum source in step (3a) is one or more of aluminum chloride hexahydrate, aluminum nitrate nonahydrate or aluminum sulfate 18hydrate; the silicon source is one or more of tetramethyl silicate, tetraethyl orthosilicate, tetraisopropyl silicate, tetrabutyl silicate or tetraphenyl silicate; wherein The silicon source, the aluminum source, ethanol, and water are mixed in a molar ratio of 1:(1-5):(10-40):(30-50).

6. The preparation method according to claim 1, characterized in that The molar ratio of propylene oxide to aluminum source in step (3b) is 1:(0.1-5); the fiber felt is one or more of aluminum silicate fiber felt, glass fiber felt or basalt fiber felt; the replacement solvent is one or more of ethanol, methanol, acetone, n-pentanol or isopropanol; the number of replacements is 5-15 times, with an interval of 6-12 hours between each replacement.

7. The preparation method according to claim 1, characterized in that The ethanol supercritical drying method described in step (3c) adopts nitrogen protection, the drying temperature is 255-280° C., the pressure of the high-pressure reactor is controlled at 8-12 MPa, and the reaction time is 2-6 hours.

8. The preparation method according to claim 1, characterized in that The coating thickness of step (4a) is 50 to 500 μm.

9. The preparation method according to claim 1, characterized in that The inert atmosphere described in step (4b) is one of argon and nitrogen or a mixture of these gases; the heat treatment temperature is 800-1500° C., the heating rate is 2-8° C. / min, and the insulation time is 0.5-5 h.

10. The preparation method according to claim 1, characterized in that The high temperature binder described in step (4c) is one or more of aluminum silicate, magnesium phosphate, sodium sulfate or potassium borate.

Citation Information

Patent Citations

  • Preparation method of high-temperature resistant silicon carbide aerogel heat-insulation composite material

    CN102910926A

  • Preparation method of flexible heat insulation composite material based on silicon-aluminum composite aerogel

    CN106747211A

  • Preparation method of light heat-insulating mullite nanofiber aerogel

    CN110078425A

  • Preparation method of fiber-reinforced Al2O3-SiO2 aerogel material with wave transmission and heat insulation integrated function

    CN106630931A

  • Lightweight flexible reusable heat-protection and heat-insulation integrated material and preparation method thereof

    CN107142715A